Introduction to Dossier: Integrating five systematic reviews of social psychology and a meta-analysis on the relationships between sense of community and well-being in Latin America and Spain - Simkin, Hugo (2025)
The results of a call for systematic reviews aimed at strengthening the cumulative integration and horizontal interaction of scientific production by Latin and Ibero American researchers in the field of social psychology are evaluated. The contributions highlight both advances and fundamental challenges for the development of a regional science. On the one hand, emerging areas of study are identified, such as coping in sexual minorities and the measurement of intergroup forgiveness, where the need to develop specific instruments and expand empirical production is emphasized. On the other hand, the existence of more consolidated critical areas of research is noted in topics such as fear of crime, social representations, and sense of community, revealing a maturing field. The dossier also highlights the relevance of innovative methodologies, such as meta-ethnography assisted by lexical analysis, and the imperative need to complement bibliometric reviews with meta-analyses. To illustrate the latter, a preliminary quantitative synthesis is presented that confirms a significant positive correlation (r = 0.32) between Sense of Community and Well-being, highlighting the potential of this line of work. In conclusion, the initiative consolidates significant progress and outlines priority routes—such as the integration of Spanish and Portuguese-language production and the promotion of quantitative syntheses—for the advancement of a Social Psychology with a regional identity.